Selecting Suitable GM (2,1) Type Model to Forecast the GDP of Iraq - Musa, Osman Rasul; Mahmood, Heshu Othman F.; aziz, Azhy akram (Sulaimani Journal for Humanities, 2022)
The budget of any country partially depends on its gross domestic product, Grey systems theory is one of the useful methods that deals with few data sets, in this study the GM(2,1) has been used to predict the GDP of Iraq, where the data took from world bank for (2008-2018) eleven periods of time, the final estimation for the parameters of the selected model depending on Delta value were as follows (r1=0.499, r2= -0.499, C1=5.438E+10 and C2=2.3055E+11) and the accuracy of the model tested through the value of the APRE which is equal to 0.03 and it is less than 0.05 this implies that the model is highly accurate
Keywords: Grey Model; GDP; GM(2; 1)